What young graduates do when they leave study – New data on the destinations of young graduates - Park, Zaneta (New Zealand Science Review, 2014)
​This report focuses on the destinations of young domestic graduates. It complements the publication ‘What young graduates earn when they leave study’, which looks at the earnings of young graduates who remain in New Zea-land. The report, focuses on differences in what graduates do rather than what they earn after they complete their studies. It looks not only at those who remain in New Zealand but also those who go overseas.The report also investigates whether trends in what graduates do after they complete their studies have changed in the last eight years or not (looking in detail at cohorts who graduated in 2003 to 2010). Comparing current figures to these historical ones helps to put current rates in perspective.